Chinese Economic Statecraft and U.S. Hegemony in Latin America: An Empirical Analysis, 2003–2014. (2nd January 2018) - Urdinez, Francisco; Mouron, Fernando; Schenoni, Luis L.; de Oliveira, Amâncio J.
Abstract: If one interprets China's sizable rise in Latin America as an unprecedented phenomenon, it follows that the concurrent story of declining U.S. influence in the region is an event hastily acknowledged at best and ignored at worst. In this article, we ask whether Chinese economic statecraft in Latin America is related to the declining U.S. hegemonic influence in the region and explore how. To do so we analyze foreign direct investments, bank loans, and international trade from 2003 to 2014, when China became a major player in the region. We use data from 21 Latin American countries, and find that an inversely proportional relationship exists between the investments made by Chinese state-owned enterprises (SOEs), bank loans, manufacturing exports, and the U.S. hegemonic influence exerted in the region. In other words, Beijing has filled the void left by a diminished U.S. presence in the latter's own backyard.